Mental health service use by young people: the role of caregiver characteristics. - Petra C Gronholm; Tamsin Ford; Ruth E Roberts; Graham Thornicroft; Kristin R Laurens; Sara Evans-Lacko (PLoS ONE)
Aims Many children and adolescents experiencing mental health problems do not receive appropriate care. Strategies to encourage appropriate access to services might be improved by a more detailed understanding of service use determinants within this group. In view of caregivers' key role in young people's pathways to care, this study aimed to advance understanding of caregiver-related characteristics that influence service use among young people. Methods We interviewed 407 primary caregivers of young people aged 9-18 years, recruited from a Greater London (United Kingdom) community sample. Caregivers reported on young people's service use in health care sector and/or education settings, and caregivers' intended stigmatising behaviours, help-seeking attitudes, and personal service use. Logistic regression analyses examined the relationship between these caregiver characteristics and young people's service use, controlling for young people's clinical and socio-demographic factors. Results Caregivers' intended stigmatising behaviours in particular exerted a strong influence on young people's service use within each service setting. The impact of this characteristic interacted with caregivers' service use in influencing young people's service use across health care and education settings and health care settings specifically. For young people's service use within education settings, caregivers' intended stigmatising behaviours score had a main effect. Conclusions This study highlights the key role caregivers' attitudes and experiences hold in young people's service use. The findings indicate that strategies aiming to bridge the gap between young people's service needs and utilisation might be improved by targeting stigma amongst caregivers.